THE FORMATION OF A HEALTHY LIFESTYLE CULTURE AMONG THE YOUTH OF UZBEKISTAN - Ochilova Faridakhon Kudrat kizi (The Conference Hub, 2025)
This article presents a comprehensive academic analysis of the importance of developing and supporting programs aimed at promoting healthy lifestyles among the youth of Uzbekistan. Emphasis is placed on their strategic role in advancing sustainable development and improving the overall quality of life within society. The study highlights the urgent need to integrate value-oriented education, health-preserving technologies, and cultural traditions into national healthcare policy. Such integration is viewed as essential for fostering a holistic and culturally sensitive approach to the socialization of young people and for cultivating a responsible attitude toward health as a fundamental personal and societal value.
Keywords: youth, health, healthy lifestyle, human socialization, values, strategy, health-preserving technologies, traditions and customs.